2017 HRS/EHRA/ECAS/APHRS/SOLAECE expert consensus statement on catheter and surgical ablation of atrial fibrillation - Calkins, Hugh (2017)
Publicado também em: https://repositorio.unifesp.br/handle/11600/53933